2016
DOI: 10.1192/s2056474000001082
|View full text |Cite
|
Sign up to set email alerts
|

Refugees, the asylum system and mental healthcare in Ireland

Abstract: The number of people seeking refugee status in Ireland is increasing year on year and the burden of mental illness experienced by refugees and asylum seekers is high. The College of Psychiatrists of Ireland has recommended the establishment of a number of specialist refugee mental health teams. In this paper we discuss the Irish asylum system, the Irish evidence regarding mental illness in this population, and current health service policy regarding refugee mental health. We propose a model of specialist refug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Working in the accommodation centres deeply affected the facilitators. It is well documented that there are significant mental health issues within direct provision centres in Ireland including depression, post-traumatic stress disorder and anxiety (O'Connell et al, 2016). Invariably as the facilitators built relationships with regular participants throughout the sessions, stories and life experiences were shared, which sometimes were traumatic.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Working in the accommodation centres deeply affected the facilitators. It is well documented that there are significant mental health issues within direct provision centres in Ireland including depression, post-traumatic stress disorder and anxiety (O'Connell et al, 2016). Invariably as the facilitators built relationships with regular participants throughout the sessions, stories and life experiences were shared, which sometimes were traumatic.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Firstly, insufficiently powered analysis, due to the small sample size, may have resulted in the failure to detect meaningful sex differences. Secondly, the complexity of the international protection process in Ireland may have contributed to participants suffering additional distress (O'Connell, Duffy, & Crumlish, 2016), further compounding any pre-departure psychological distress. It must also be noted that the population in this study were treatment-seeking and therefore the prevalence rates are likely an overestimation of true prevalence rates of PTSD and CPTSD among asylum seekers and refugees who have experienced torture.…”
Section: Discussionmentioning
confidence: 99%
“…Both delays in the international protection process and difficulties accessing autonomous housing have resulted in international protection beneficiaries remaining in IPAS centres for years at a time. 302 Previous research in Ireland has found that refugees have a high prevalence of psychological issues due to traumatic experiences and post-migration stressors such as insecure residency (O'Connell et al, 2016). In addition, living in the Direct Provision system has been found to have negative psychological impacts, reducing personal autonomy and self-esteem (Crosscare Refugee Service, 2018; College of Psychiatrists of Ireland, 2017; Foreman and Ní Raghallaigh, 2015;Stewart, 2006), and increasing dependency (Ní Raghallaigh et al, 2016), which can then pose a further challenge for those trying to find autonomous housing.…”
Section: Psychological Issuesmentioning
confidence: 99%
“…Previous research on the housing experiences of migrants in rural Ireland has found that employment influences a migrant's access to housing and shapes their subsequent housing trajectories (Finn and Mayock, 2021). However, it should be noted that a person's employment opportunities and their ability to engage in the labour market can also be adversely affected by the international protection system in Ireland deposits or additional income to top-up HAP payments (Bieri, 2024;Polakowski and Cunniffe, 2023;Doras, 2021;McGinnity et al, 2020;Duffy and Crumlish, 2016).…”
Section: Employmentmentioning
confidence: 99%